Micro manipulation by a compliant piezoelectric micro gripper towards robotic micro assembly. (2016) - Jain, Ravi Kant; Majumder, Somajyoti; Ghosh, Bhaskar; Saha, Surajit
This paper presents a new design of mobile micro manipulation system for robotic micro assembly where a compliant piezoelectric actuator-based micro gripper is designed for handling the miniature parts. The compensation of misalignment during robotic peg-in-hole assembly is achieved by this compliant micro gripper because the piezoelectric actuator has capability of producing the displacement in micron range and generates high force instantaneously. The throughput/speed analysis of mobile micro manipulation system is carried out for picking and placing the peg from one hole to next hole position. An analysis of piezoelectric actuator-based micro gripper has also been discussed where voltage is controlled through a proportional-derivative (PD) controller. By developing a prototype, it is demonstrated that compliant piezoelectric actuator-based micro gripper is capable of handling the peg-in-hole assembly task in a mobile micro manipulation system.